Case Study: The Concept of 'Religious Tolerance' in the Socio-Religious Construction of Islamic Schools in India - Naeem, Ayesha Fakhar; Yousaf, Esha Momena (Institut Agama Islam Negeri Lhokseumawe, 2023)
This study explores the strategies and challenges involved in managing religious tolerance in Islamic schools in India. This study specifically examines the implementation of education in Dar-ul Madinah international Islamic School System and Al Hira International Islamic School, both of which follow Islamic principles. The study utilizes a descriptive qualitative survey methodology to gather insights from key stakeholders such as school administrators, teachers, and students. By employing this methodology, the research seeks to understand the strategies Islamic the school employs to promote religious tolerance and identify the obstacles they face. Since Islam is a minority religion in India, these schools encounter unique challenges. findings will contribute to the existing knowledge on religious tolerance in the Indian educational landscape and provide valuable insights for school administrators, policymakers, and educators. Dar-ul Madinah international Islamic School System and Al Hira Islamic School is a model for promoting religious tolerance by implementing best practices in curriculum design, interfaith dialogue, and creating an inclusive environment. By adopting these strategies, the school fosters an environment where students understand Islam comprehensively, engage in positive interactions with other faiths, and experience the benefits of a diverse and inclusive community. Additionally, the management of these schools prioritizes religious tolerance, allowing students to adapt and coexist harmoniously with the majority Hindu community. The study examines the educational practices of these schools in alignment with their vision and mission. It proposes strategies for implementing religious tolerance-based education, which can serve as a blueprint for Islamic schools in minority countries.